0158 Neuronal Projection From Preoptic Hypothalamus To Sublaterodorsal Nucleus. (27th April 2018) - Hsieh, K; Kumar, S; Chase, M H; Szymusiak, R
Abstract: Introduction: Our previous study shows that a population of neurons in the dorsolateral preoptic area (DLPO) exhibit REM sleep-related discharge (Alam et al, 2014). In the current study we investigate the anatomical connections from the preoptic area including DLPO to the sublaterodorsal nucleus (SLD), a pontine region which is critical in REM sleep control. Methods: Adult Sprague-Dawly rats received unilateral injection of the retrograde tracer cholera toxin subunit-b Alexa Fluor 594 conjugate (CTb), targeting the SLD. The rats were euthanized after a 7-day survival period to allow for retrograde transport of tracer. The brain tissues were sectioned and processed for immunohistochemistry for glutamic acid decarboxylase (GAD), a marker of GABAergic neurons. CTb-labeled and GAD-labeled neurons were traced and counted in the animals with tracer injection on target. Results: A small population of CTb-labeled projection neurons was seen in DLPO (13.3 ± 2.9), MnPN (11.6 ± 0.9), and VLPO (1.0 ± 1.0). (Mean ± SEM, count per section on ipsilateral side to tracer injection). No GABAergic projections from the preoptic area to the SLD were found. Conclusion: Together with the results from our previous studies showing a substantial number of projection neurons from POA to ventrolateral periaqueductal gray (vlPAG) (Hsieh et al, 2011; Kumar et al., 2016), we hypothesize that preoptic modulation of REM sleep regulatory neurons in the SLD is mediated through projections to the vlPAG. An effort to confirm the functional activity of these POA projection neurons by examining c-Fos activation in relationship with REM sleep is in progress. Support (If Any): NS092383 and VA Merit Award BX00155605.